Analysis of kepok banana (musa paradisiaca l) stems and roots extract in inhibiting the growth of candida albicans - Harlina Harlina; Nadiah G. Azizah (DiscoverSys Inc., 2019)
Objective: The aim of this study to analysis the effectiveness of kepok banana (Musa paradisiaca L)Â stems and roots extract in inhibiting the growth of Candida albicans and determining part of stem or root that is more effective in inhibiting the growth of Candida albicans (a number of colonies).Material and Methods: This study was an experimental study with a dilution method. The samples were Candida albicans colonies. The extraction was conducted using methanol maceration method. Viscous extracts were diluted using 10% dimethyl sulfoxide and filtered with Whatman paper filter. Those extracts were then divided into three separate groups; K(control), B(stem), A(root). Groups K, B and A were added with Potato Dextrose Broth (PDB) media to reach concentrations of 25%, 12.5%, and 6.25%. The amount of Candida albicans colonies were counted and statistically analyzed using ANOVA and Post Hoc.Results: Kepok Banana stems and roots extract was effective in inhibiting the growth of Candida albicans (a number of colonies). Root extract concentration of 25% had a better inhibitory effect compared to 12.5% and 6.25% concentration on both extracts. Root extract is better than stem extract.Conclusion: Extracts of kepok banana stems and roots (musa paradisiaca l.) are effective in inhibiting the growth of candida albicans.